Baltetin: a new C-type lectin-like isolated from Bothrops alternatus snake venom which act as a platelet aggregation inhibiting - Pereira, Déborah Fernanda da Cunha; Matias Ribeiro, Mariana Santos; de Sousa Simamoto, Bruna Barbosa; Dias, Edigar Henrique Vaz; Costa, Júnia de Oliveira; Santos-Filho, Norival Alves [UNESP]; Bordon, Karla de Castro Figueiredo; Arantes, Eliane Candiani; Dantas, Noelio Oliveira; Silva, Anielle Christine Almeida; de Oliveira, Fábio; Mamede, Carla Cristine Neves (Elsevier, 2021)
C-type lectin-like proteins found in snake venom, known as snaclecs, have important effects on hemostasis through targeting membrane receptors, coagulation factors and other hemostatic proteins. Here, we present the isolation and functional characterization of a snaclec isolated from Bothrops alternatus venom, designated as Baltetin. We purified the protein in three chromatographic steps (anion-exchange, affinity and reversed-phase chromatography). Baltetin is a dimeric snaclec that is approximately 15 and 25 kDa under reducing and non-reducing conditions, respectively, as estimated by SDS-PAGE. Matrix-assisted laser desorption and ionization time-of-flight mass spectrometry and Edman degradation sequencing revealed that Baltetin is a heterodimer. The first 40 amino acid residues of the N-terminal region of Baltetin subunits share a high degree of sequence identity with other snaclecs. Baltetin had a specific, dose-dependent inhibitory effect on epinephrine-induced platelet aggregation in human platelet-rich plasma, inhibiting up to 69% of platelet aggregation. Analysis of the infrared spectra suggested that the interaction between Baltetin and platelets can be attributed to the formation of hydrogen bonds between the PO32- groups in the protein and PO2- groups in the platelet membrane. This interaction may lead to membrane lipid peroxidation, which prevents epinephrine from binding to its receptor. The present work suggests that Baltetin, a new C-type lectin-like protein isolated from B. alternatus venom, is the first snaclec to inhibit epinephrine-induced platelet aggregation. This could be of medical interest as a new tool for the development of novel therapeutic agents for the prevention and treatment of thrombotic disorders.
Keywords: Bothrops alternatus; Platelet aggregation; Snaclecs; Snake venom